Pelatihan Pengembangan Soal HOTS dengan Memanfaatkan Quizizz untuk Guru Sekolah Dasar Pedesaan - Afib Rulyansah (Utan Kayu Publishing, 2021)
The Covid-19 pandemic condition triggered teachers to adjust their attitudes to existing conditions. Learning in the network (online) must be chosen so that the teaching process can still be carried out. However, teachers were not used to compiling HOTS evaluations online using the Quzizizz application. This community service program aimed to provide assistance in preparing HOTS questions using the Quizizz application. The training was carried out during the Covid-19 pandemic online for elementary school teachers in the Tiris District, Problinggo Regency. The results show that in general teachers are said to be able to conduct online evaluations by utilizing the Quizizz application. All teachers were present in all training meetings, teachers were also able to create Quiziz Accounts. HOTS questions on Quizizz were also able to be made by the majority of teachers so that they can activate students' higher-order thinking skills. All teachers tried out the HOTS questions that had been made to their respective students. This training has a significant impact on the ability of teachers to develop HOTS-type online evaluation questions using the Quizizz application.